2020
DOI: 10.1088/1757-899x/985/1/012029
|View full text |Cite
|
Sign up to set email alerts
|

Study of strength characteristics of the long wheelbase flat cars

Abstract: Transportation of goods in large containers with loading length of 80 feet is one of the promising directions of railway transport development. However, despite considerable experience in construction of long-wheelbase flat cars, occasionally problems with the strength of load-bearing elements arise at the calculation, design and manufacture of such products. The article presents the technical characteristics of a long wheelbase flat car, as well as the results of experimental studies of fatigue tests of its l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The National Transport Strategy until 2030 identifies the development of rolling stock as one of the most important areas of development of railroads in Ukraine. Ensuring the competitiveness of the railroad industry necessitates the commissioning of modern rolling stock structures with improved technical, economic, and operational indicators [1,2]. In addition, the design of such rolling stock should provide the ability to reduce the cost of its maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…The National Transport Strategy until 2030 identifies the development of rolling stock as one of the most important areas of development of railroads in Ukraine. Ensuring the competitiveness of the railroad industry necessitates the commissioning of modern rolling stock structures with improved technical, economic, and operational indicators [1,2]. In addition, the design of such rolling stock should provide the ability to reduce the cost of its maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…In the papers [11,12], the main ways of increasing the degree of ideality of freight wagons and the development of the running gear of the new generation cars, taking into account the dynamic loads that affect these wagons and their running gears during operation, are determined. In the papers [13,14], the results of dynamic load simulation of containers and the study of their stability, placed on flat cars during railway ferry transportation, are presented.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, according to the results of the literature source analysis [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], it can be concluded that the issues of determining the dynamic load of tank containers during transportation on a rail ferry have not been fully studied so far. At the same time, the determination of the dynamic load of tank containers as part of mixed trains with tank cars during the formation of a traction connection before loading onto a railway ferry and during shunting operations (roll on/roll off) on the lower and upper decks of a railway ferry was not investigated in these works, though it is one of the main stages of the tank container testing.…”
Section: Introductionmentioning
confidence: 99%